2019
DOI: 10.15407/ujpe64.3.238
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Polymer Clusters in Aqueous Solutions of Hydroxypropyl Cellulose

Abstract: The viscosity, turbidity, and heat capacity of dilute aqueous solutions of hydroxypropyl cellulose have been studied in a concentration interval of 0.047-1.5 g/l and a temperature interval of 20-80 ∘ C. The data obtained testify that, if the temperature does not exceed 40 ∘ C, hydroxypropyl cellulose molecules are prolate spheroidal globules with semiaxis lengths of 7 and 490Å. At temperatures above 70 ∘ C, the hydroxypropyl cellulose solution consists of clusters; every cluster is composed of 11 globules and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 5 publications
0
12
0
1
Order By: Relevance
“…The form of molecules in a solution was determined according to the data of the viscometric experiment (the relevant procedure was described in work [4]). Aqueous solutions of metolose manufactured by the Shin-Etsu Chemical Company (Hypromellose USP, Substitution Type 2906, Grade 65SH-50) were studied [3].…”
Section: Forms Of Molecules and Their Clusters In A Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The form of molecules in a solution was determined according to the data of the viscometric experiment (the relevant procedure was described in work [4]). Aqueous solutions of metolose manufactured by the Shin-Etsu Chemical Company (Hypromellose USP, Substitution Type 2906, Grade 65SH-50) were studied [3].…”
Section: Forms Of Molecules and Their Clusters In A Solutionmentioning
confidence: 99%
“…Therefore, the mechanisms of the mentioned structural transition will be studied on an example of the cellulose derivative, hy-droxypropyl methylcellulose (metolose) [3]. To some extent, this article continues our work [4].…”
Section: Introductionmentioning
confidence: 95%
“…Currently, the mechanism of gelation has not been studied enough yet despite the existence of a number of relevant hypotheses (see, e.g., works [10][11][12][13]). Earlier, we studied the thermally induced change in the macromolecular conformation of cellulose derivatives in highly dilute aqueous solutions [14,15]. It was shown that the examined sol-gel transition in those systems has a character typical of the phase transition of the first kind.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 illustrates the scheme of the experimental setup, which is an improved version of the device used in [13] for turbidity measuring.…”
Section: Methodsmentioning
confidence: 99%